2022
DOI: 10.7759/cureus.23822
|View full text |Cite
|
Sign up to set email alerts
|

A Case of New-Onset Atrial Fibrillation With Rapid Ventricular Response Due to Iatrogenic Hypothermia

Abstract: Hypothermia is an involuntary fall in body temperature, usually below 35°C. Hypothermia is a common condition, especially in frigid zones. However, it should not be forgotten that it can also occur in temperate climates or for iatrogenic reasons. Hypothermia is associated with seriously severe arrhythmias, particularly ventricular fibrillation, and there are many reports of prolonged resuscitation in these patient groups. This case report shows that a standard thermometer, either with Emergency Medical Service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Evidence suggests that substantial progress has been made in diagnosing and treating ACS, mainly in high-income countries [ 28 , 29 ]. However, the results of the current study showed that not all ACS patients eligible to be reviewed and assessed by cardiologists have accessed cardiologists for their check-ups.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that substantial progress has been made in diagnosing and treating ACS, mainly in high-income countries [ 28 , 29 ]. However, the results of the current study showed that not all ACS patients eligible to be reviewed and assessed by cardiologists have accessed cardiologists for their check-ups.…”
Section: Discussionmentioning
confidence: 99%